Participacija v prostorskem planiranju - Ploštajner, Zlata (Urbani izziv, 2003)
Physical planning is also a political activity. Therefore participation is a necessary form of democratic actions undertaken by individuals and groups thatstrive for democratisation of civil society and strengthening of democratic social values. Public participation of citizens, legal subjects, interest groups and others in physical planning is essential even from the aspect of ensuring success and efficiency of planning documents, if the idea is to devise a plan, which the people would be ready and capable of implementing. Thus the role of the physical planner is changing from technicalexpert to mediator or anchor-person, who nevertheless has to operate within a normative framework.
Keywords: autonomy; avtonomija; decentralizacija; democracy; demokracija; javno mnenje; javnost; prostorsko planiranje; spatial planning